Ideomotor Apraxia in Left Thalamic Hemorrhage: Discrepancy between Clinical Course and SPECT - Armin Schnider; Theodor Landis; Helmuth R. Rösler (Behavioural Neurology)
We present a patient who developed severe ideomotor apraxia (IA) and subcortical aphasia after a hemorrhage involving the posterior part of the left thalamus and the posterior limb of the internal capsule. The cerebral blood flow (CBF) of the left hemisphere as measured by 99Tc-HM-PAO SPECT was initially diminished as compared to the right hemisphere. The apraxia and aphasia eventually resolved. Despite this clinical improvement CBF of the left hemisphere worsened. Our findings do not support the view that apraxia and aphasia following lesion of deep subcortical structures is due to cortical derangement induced by disruption of unspecific activating thalamo-cortical pathways. The results call for caution in the functional interpretation of perfusion deficits detected by SPECT.